Neurotrophins and the BBB - Pan, Weihong (Henry Stewart Talks, 2008)
Overview of neurotrophins, CNS physiology and roles in neuroregeneration, The blood-brain barrier (BBB), General strategies to enhance CNS delivery, Progress on neurotrophin delivery across the BBB, Limitations and future directions
Archived at 2017/01/31